Analisa Risiko pada Rantai Pasok Industri Beton Pracetak Sistem Make-to-Order - Desy Ratna Arthaningtyas; Nurti Kusuma Anggraeni; Seno Suharyo (Universitas Batanghari Jambi, 2023)
The precast concrete supply chain has a long process and timeframe which often becomes an obstacle in its implementation. Like what happened to PT. X which is one of the precast concrete industrial companies located in the city of Semarang. In the supply chain work method at PT. X implements a make-to-order (MTO) system in which precast products will begin to be produced if they have received direct orders from consumers so that the finished time of precast products can adjust to the time of project implementation in the hope that the products are still in new and good condition. Long supply chain processes often cause problems or risks in their performance. To be able to find out what risks arise in the process of supply chain stages, it is necessary to have a risk analysis in the supply chain of the precast concrete industry. Risk analysis is carried out by first identifying the risks that may arise, then calculating the analysis by multiplying the probability and the impact of the risks that arise. Probability value and risk impact on PT. X was obtained from the results of questionnaires and interviews conducted with all employees. Based on the results of the analysis, it is known that the risk with the highest level is the